2017
DOI: 10.1108/ijcthr-09-2015-0115
|View full text |Cite
|
Sign up to set email alerts
|

Digging deep into the experience – flow and immersion patterns in a mountain holiday

Abstract: Purpose This paper aims to provide a longitudinal study of a five-day tourist stay in a mountain resort, where flow and immersion are analysed to understand how consumers experience and construct their holiday stay. The need to process to a longitudinal study is motivated by the lack of research looking at what actually happens during the experience. More precisely, the long encounter of a holiday is often disregarded, and the tourist experience is studied afterwards through single and comprehensive satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
3
29
0
1
Order By: Relevance
“…In the context of commercial hospitality (nightclubs), Taheri et al (2017) found that play (consisting of flow, community and ecstasy) influences involvement, happiness and enjoyment. In another recent study, Frochot et al (2017) found that flow experiences during (mountain) holidays are related with sport activities, but also with social cohesion and landscape beauty. In a study that also examined flow on the group (family) level, Larsen (2013) established that intra-family dynamics create a social balance or family flow, which is an important factor of being together.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 96%
“…In the context of commercial hospitality (nightclubs), Taheri et al (2017) found that play (consisting of flow, community and ecstasy) influences involvement, happiness and enjoyment. In another recent study, Frochot et al (2017) found that flow experiences during (mountain) holidays are related with sport activities, but also with social cohesion and landscape beauty. In a study that also examined flow on the group (family) level, Larsen (2013) established that intra-family dynamics create a social balance or family flow, which is an important factor of being together.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 96%
“…These two concepts of escapism and immersion are core to the tourism experience (Carù and Cova 2003) and interrelated. As Frochot, Elliot, and Kreziak (2017) note in a study of tourists in a mountain resort, immersion closely ties in “with the feeling of getting away: the more immersed they got, the more they forgot about everyday life” (p. 87), indicating that the feeling of escapism derives from being immersed in the experience. Put differently, when people immerse “in” the experience, they escape “from” their reality.…”
Section: Study 1: a Field Study At A Wine And Spirit Tourism Attractionmentioning
confidence: 98%
“…7 for future investigations on the nature of immersion) [4]. Flow is an extreme experience [3,6,53], which limits it to optimal, positive experiences. Additionally, the absence of key components of flow (e.g., balance between ability and challenge, clear goals, and immediate feedback) in activities such as watching a movie or listening to music essentially disqualifies passive activities as flow experiences.…”
Section: Flowmentioning
confidence: 99%